Counseling on Pre-Menstrual Syndrome (PMS) In Adolescents - Fresthy Astrika Yunita; Hardiningsih - -; Agus Eka Nurma Yuneta (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Background: Premenstrual Syndrome (PMS) is the most common health problem reported by adolescents. The main contributing factors of PMS are due to the imbalance of work of the hormones estrogen and progesterone’s as well as changes in serotonin levels. Approximately 30-80% of women experience mood or somatic disorders (or both) that occur during the menstrual cycle. The WHO (World Health Organization) report explains that PMS symptoms are experienced in 65.7 of young women. Due to lack of knowledge can decrease the quality of life of adolescents. So the knowledge about PMS is needed for young women to be ready to face the PMS.Purpose: Improving young women's knowledge of PMS.Method: The provision of PMS material was done by lecture method and leaflet giving. The object of devotion was young women. Before the counseling being given, young women took pre-tests, later conducted post-tests to evaluate the knowledge related to PMS. Result: Counseling on PMS had been conducted. There was an increased in young women's knowledge of Premenstrual Syndrome. T-test results obtained significance value of 0.000 (p<0.005).Conclusions and Suggestions: Counseling has a positive effect on young women's knowledge, especially about PMS. Pkd Wonorejo midwives should be able to provide regular counseling for young women. For the young women, after the counseling obtained results that can increase knowledge about PMS thus that it is expected to be better prepared to face the PMS